PENGARUH METODE LATIHAN SISTEM SET DAN SIRKUIT TERHADAP PENINGKATAN KEMAMPUAN DAYA LEDAK OTOT LENGAN PADA ATLET BOLABASKET FIK UNP - Sari Mariati; Willady Rasyid (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
This study aims to see whether or not there is a difference in the influence of the set system and circuit system on the increase in arm muscle explosive power in UNP Padang FIK athletes. This type of research is a quasi-experimental research conducted at the PPSP GOR of UNP Development. This study aims to see whether or not there is a difference in the influence of the set system and circuit system on the increase in arm muscle explosive power in UNP Padang FIK athletes. The type of this research was a quasi-experimental study conducted at the PPSP National Development Development Center in the sample. The research was 20 male football players from FIK UNP and consisted of 10 sets of system groups and 10 circuit system groups who were given 16 exercises Data collection techniques using two hand medicine ball push. The collected data is used to test hypotheses using the t test. Before the t test is carried out, the analysis requirements test is carried out, namely the normality test and homogeneity test. The results of the 1.2, and 3 hypothesis test using t test statistics can be summarized as follows: (1) The set system does not significantly influence the increase in arm muscle explosive ability. It can be obtained thit 1.74 <ttab 2.26 and p 0.11> 0.05α. > tt2.26 and p 0.00 <0.05α (3) There is no significant difference in effect between the set system and the circuit system on the increase in arm muscle explosive ability, the value of thit 1.32 <2.26 and p 0.287> 0.05α.